Person, scholar, citizen (living memory of Vazha Keshelava) - Siamashvili, Gia (Politics / პოლიტიკა, 2020)
The author recalls episodes of his 20 years of cooperation with Vazha Keshelava, who reveals him as a scholar and a person.